Knocking on heaven's door : the path to a better way of death - Butler, Katy, 1949- (New York : Scribner, 2013)
"A blend of memoir and investigation of the choices we face when our terror of death collides with the technological imperatives of modern medicine"--
Includes bibliographical references.
Keywords: Terminal care; Terminal care -- Decision making; Euthanasia -- Moral and ethical aspects; Adult children of aging parents -- Family relationships